2004
DOI: 10.1158/1078-0432.ccr-04-0389
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β (ERβ) Level but Not Its ERβcx Variant Helps to Predict Tamoxifen Resistance in Breast Cancer

Abstract: The antiestrogen tamoxifen, a major endocrine therapy of estrogen receptor (ER)-positive breast cancer, is nevertheless inefficient in 30 to 40% of cases for unknown reasons. We retrospectively studied 50 ER-positive primary breast carcinomas. All of the patients had received tamoxifen as the only adjuvant therapy. They were divided into two groups depending on whether they relapsed within 5 years (16 tamoxifen-resistant cases) or did not relapse within 5 years (34 tamoxifen-sensitive cases). The expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
100
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 34 publications
7
100
1
3
Order By: Relevance
“…In patients treated with chemotherapy as well as TAM, ERβ expression also significantly correlates with increased OS [97,105] and DFS [94,97,104,105]. Higher ERβ expression is observed more frequently in TAM-sensitive breast tumors than in TAM-resistant tumors [113], and lower ERβ is associated with TAM resistance [107,113,114]. One study analyzing 138 postmenopausal patients with invasive cancer observed a trend toward worse outcome in ERβ+ patients treated with TAM, although it was not statistically significant and only seventeen ERβ− tumors were used in this comparison.…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 99%
See 4 more Smart Citations
“…In patients treated with chemotherapy as well as TAM, ERβ expression also significantly correlates with increased OS [97,105] and DFS [94,97,104,105]. Higher ERβ expression is observed more frequently in TAM-sensitive breast tumors than in TAM-resistant tumors [113], and lower ERβ is associated with TAM resistance [107,113,114]. One study analyzing 138 postmenopausal patients with invasive cancer observed a trend toward worse outcome in ERβ+ patients treated with TAM, although it was not statistically significant and only seventeen ERβ− tumors were used in this comparison.…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 99%
“…Iwase et al have reported that patients with ERβ+ tumors tend to have a better response to endocrine therapy than those with ERβ− tumors [112]. In breast cancer patients treated with adjuvant TAM, high ERβ expression significantly correlates with increased overall [86,107] and disease-free survival [107], no disease progression [113], or no relapse within five years [93,114]. In patients treated with chemotherapy as well as TAM, ERβ expression also significantly correlates with increased OS [97,105] and DFS [94,97,104,105].…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 99%
See 3 more Smart Citations